La “ayuda familiar” como medida de fomento del empleo y/o del autoempleo en tiempos de crisis: estado de la cuestión en España y propuestas de reforma - Barrios Baudor, Guillermo L. (Revista de Derecho, 2019)
In not few cases, autonomous workers receive formal and/or informal help from theirclosest relatives. Therefore, on the basis of Spanish legal ordainment, the present workhas as its main objective to present the granting of services in the modality of “familyhelp or collaboration” as a real employment and/or self-employment opportunity intimes of crisis. More specifically, what we pretend to do is but highlight the virtualityof family collaboration in generating formal employment (in contrast to the frequentlyinformal), whether in the modality of paid employment or in self-employment. In noway should it be regarded as a second class modality of service granting.
Keywords: autonomous work; family collaboration; family work